1995
DOI: 10.1111/j.1365-2958.1995.mmi_17030449.x
|View full text |Cite
|
Sign up to set email alerts
|

The extreme C‐terminus is required for secretion of both the native polygalacturonase (PehA) and PehA‐Bla hybrid proteins in Erwinia carotovora subsp. carotovora

Abstract: A set of gene fusions was constructed between the pehA gene encoding the secreted endopolygalacturonase (PehA) and the bla gene coding for a normally periplasmic beta-lactamase (Bla). The resulting hybrid proteins were specifically and actively routed out of the cells via the Out-terminal branch of the general secretory pathway (GSP) in Erwinia carotovora subsp. carotovora (Ecc), provided that no more than the last two amino acids (aa) of the PehA domain were excluded from the fusion. However, both PehA-Bla hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In the case of P. aeruginosa PE, residues 60 to 120 appeared to be sufficient for directing ␤-lactamase secretion (26). However, in the case of E. carotovora polygalacturonase (PehA), no more than the last two amino acids of the PehA could be excluded from a PehA-Bla hybrid without blocking secretion (29,30). Passenger proteins might contain structures incompatible with efficient secretion by the type II machineries.…”
Section: Fig 4 Secretion By P Aeruginosa Pak-nt Of Pe and The Pe Dmentioning
confidence: 99%
“…In the case of P. aeruginosa PE, residues 60 to 120 appeared to be sufficient for directing ␤-lactamase secretion (26). However, in the case of E. carotovora polygalacturonase (PehA), no more than the last two amino acids of the PehA could be excluded from a PehA-Bla hybrid without blocking secretion (29,30). Passenger proteins might contain structures incompatible with efficient secretion by the type II machineries.…”
Section: Fig 4 Secretion By P Aeruginosa Pak-nt Of Pe and The Pe Dmentioning
confidence: 99%
“…Studies on many different type II substrates have identified a large variety of domains and amino acids that are required for secretion (Hamood et al 1989;Kornacker and Pugsley 1990;He et al 1991b;Wong and Buckley 1991;Py et al 1993;Palomaki and Saarilahti 1995;Sauvonnet et al 1995;Lu and Lory 1996). For example, two spatially separated domains of pullulanase (PulA) seem required for substrate recognition (Sauvonnet and Pugsley 1996).…”
Section: Components Of the General Secretory Pathway And Substrate Rementioning
confidence: 99%
“…It was also suggested that P. aeruginosa exotoxin A (ToxA) contains two separate secretion signals [132], while alteration of another region also affects secretion efficiency [133]. Finally, the polygalacturonase PehA of E. carotovora was found to contain three separate domains involved in T2SS targeting [134,135]. As reported above, the secretion signal may be composed of residues from different locations in the linear polypeptide chain, which are brought together into a conformational patch during protein folding [136].…”
Section: Substrate Recognition and Transport By The T2ss Machinementioning
confidence: 96%